Transformation of Religious Moderation Education in the Ideology of Hizmet Fethullah Gulen - Pimada, Muhammad Alfaqih; Ghazi, Ghazi (Faculty of Education and Teacher Training of UINSI Samarinda, 2023)
Religious moderation education is an effort to teach a balanced and tolerant understanding of religion, promote interfaith dialogue, and minimize the potential for conflict, with the aim of building harmony between religious communities. Gulen's ideology in the realm of education has the main goal of forming a person's character in respecting diversity, strengthening the values of peace, and creating an inclusive learning environment. So the research is qualitative-based in the form of literature study and context analysis. The three main works of Hizmet Fethullah Gullen's Ideology studied are Tasawuf untuk Kita Semua; Wa Nahnu Nuqimu Sharh Al-Ruh; and Islam Rahmatan lil Alamin. The results of this research are the promotion of inclusive education, interfaith dialogue, and the development of social skills. The focus on character education, interfaith dialogue, and social skills development aims to form individuals who are academically intelligent and have strong moral values. Through the application of values such as tolerance and social service, Hizmet Gulen's ideology seeks to create an inclusive, peaceful and just society.